A learner-centric model of learning organizations. Issue 1 (15th October 2020) - Akella, Devi
Abstract : Purpose: This paper aims to contribute by placing the missing "learner agent" within the entire process of learning. To understand under what social conditions, it is possible to develop autonomous learners who are conscious of self, able to reflect on their identities, roles and responsibilities, to learn and develop professionally, in alignment with the organizational goals and objectives. Design/methodology/approach: The paper uses empirical data from a higher educational institution to provide insights on how it might be possible to intervene to incorporate workspaces which allow learner agent reflection resulting in individual and organizational learning processes, devoid of power exercises and manipulation strategies. Findings: The empirical findings reveal the crucial role of learner agents, and positive outcomes associated with learning that happens be an autonomous choice and process, with minimal structural influence. The relevance of reflection, personal identity, social conditions, dialogic third spaces and transformation opportunity structures in developing lifelong learners, learning societies and democratic learning organizations is emphasized. Research limitations/implications: This study suggests plausible directions in which the model of learning organizations can move forward, in the form of designing transformation structures or workspaces where learner agents have the opportunity to reflect on their tacit knowledge, job responsibilities and functions in an autonomous manner to generate learning, which is democratic and un-contested in nature. Originality/value: The significance of learner agent in the entire learning process is demonstrated, to place forward a learner-centric model of learning organization where structure and agency harmoniously merge to form one common ground, where individual learning becomes organizational learning with no hidden power dynamics. Empirical evidence is provided to demonstrate how learning can be a win–win situation for all organizational groups.